INFLUENCE OF THREE NUTRIENT SOLUTIONS: HOAGLAND, TC MOBI AND KNOP ON THE GROWTH, FRUIT YIELD AND QUALITY OF HYDROPONIC TOMATO CHANOKA F1 - Huyền, Trần Thị Thanh; Tuyến, Đặng Thị; Thủy, Lê Thị; Bằng, Cao Phi (Hue University Journal of Science: Natural Science, 2017)
The nutrient solution is an important factor which directly affects the growth, yield, and quality of hydroponic crops. In this study, the effects of three common nutrient solutions, namely Hoagland, Knop and TC Mobi on the growth, yield, and fruit quality of tomato Chanoka F1 variety were evaluated. The results showed that the Hoagland solution had more positive influence on the growth, yield and fruit quality characteristics of tomato Chanoka F1 than the other two solutions. The plants grown in the Knop solution had the smallest yield and the poorest fruit quality. In addition, the nitrate content in the fruits was within the limit set by WHO for all of the three studied hydroponic solutions.